The Intergenerational Transmission of Cognitive and Non-Cognitive Abilities - Erik Grönqvist; Jonas Vlachos; Björn Öckert (Research Institute of Industrial Economics (IFN), 2011)
We study the intergenerational transmission of cognitive and non-cognitive abilities between fathers and sons using population-wide enlistment data. Measurement error bias in fathers ability measures is corrected for using two sets of instruments. Results suggest that previous estimates of intergenerational ability correlations are biased downwards; once corrected for, the non-cognitive correlation is close to that of cognitive ability. We also predict mothers abilities and find the mother-son cognitive ability correlation to be stronger than the father-son correlation. Finally, educational attainment and labor market outcomes of both sons and daughters are strongly related to both parents cognitive and non-cognitive abilities.
Keywords: I00; J13; J24; 330; Intergenerational Ability Correlations; Cognitive Ability; Non-Cognitive Ability; Measurement Error Bias; Intelligenz; Persönlichkeitspsychologie; Generationengerechtigkeit; Eltern; Mütter; Kinder; Jungen; Schweden